1970
DOI: 10.1037/h0029584
|View full text |Cite
|
Sign up to set email alerts
|

Visual and haptic dimensional preference: A developmental study.

Abstract: Dimensional preference tasks in bcth visual and haptic modalities with three dimensional stimuli varying in form, size, color, or texture were presented to 64 children. There were 16 subjects at each of four grade levels: preschool, kindergarten, grade 1, and grade 3. On each trig'., the subject was presented three stimuli and asked to tell the exami:er which two were the same. The pattern of preference scores was essentially the same in bath visual and haptic tasks. On both tasks, all age groups, except for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Following the notion that form-based object-naming and classification is habitual and automatic in children (Kagan and Lemkin, 1961; Siegel and Vance, 1970; Bloom, 2002; Diesendruck and Bloom, 2003), Prevor and Diamond (2005) have used a color-object Stroop task, asking young children to name the colors of abstract shapes and familiar objects, which were presented in their congruent (e.g., a yellow banana), incongruent (e.g., a blue banana), or neutral (e.g., a purple scissors) colors. Because of their stimulus-driven tendency to name the objects, children were slower and less accurate in naming the color of namable objects in comparison to abstract forms, even when the objects appeared in their congruent colors.…”
Section: Task Conflict In the Context Of Stimulus-driven Behaviorsmentioning
confidence: 99%
“…Following the notion that form-based object-naming and classification is habitual and automatic in children (Kagan and Lemkin, 1961; Siegel and Vance, 1970; Bloom, 2002; Diesendruck and Bloom, 2003), Prevor and Diamond (2005) have used a color-object Stroop task, asking young children to name the colors of abstract shapes and familiar objects, which were presented in their congruent (e.g., a yellow banana), incongruent (e.g., a blue banana), or neutral (e.g., a purple scissors) colors. Because of their stimulus-driven tendency to name the objects, children were slower and less accurate in naming the color of namable objects in comparison to abstract forms, even when the objects appeared in their congruent colors.…”
Section: Task Conflict In the Context Of Stimulus-driven Behaviorsmentioning
confidence: 99%
“…A stimulus is considered to "be" what its object classification or name is, while color is but one of its surface attributes. Children and adults are inclined to classify and sort by shape (or object kind) rather than by color (Colby & Robertson, 1942;Kagan & Lemkin, 1961;Mittler & Harris, 1969;Siegel & Vance, 1970;Smiley & Weir, 1966;Rosch, Mervis, Gray, Johnson, & Boyes-Braem, 1976) and to generalize a new word or fact to other stimuli of the same shape or object kind rather than to other stimuli of the same color (termed "the shape bias" by Landau, Smith, & Jones, 1988; see also Gelman & Markman, 1987;Smith, Jones, Gershkoff-Stowe, & Samuelson, 2002).…”
Section: Why Should Object-naming Be Prepotent Over Color-naming?mentioning
confidence: 99%
“…What is clear is that over development children come to attend preferentially to form more and more. There is much evidence that during early childhood there is a progression from preferential focusing on color to preferential focusing on shape, with 3-4½ years of age being the peak of the preference for color or a transition period of equal preference for color and form (Brian & Goodenough, 1929;Brown & Campione, 1971;Colby & Robertson, 1942;Corah, 1964;Descoudres, 1941;Kagan & Lemkin, 1961;Melkman & Deutsch, 1977;Siegel & Vance, 1970;Suchman & Trabasso, 1966;Tobie, 1926). For example, Suchman and Trabasso (1966) found that when they asked children to "point to the two that are the same," children of 2.8-3.9 years preferred color, children of 3.9-4.5 showed no net preference, and children of 4.5-5.5 years preferred form, with the difference between form and color preference increasing significantly and linearly with age.…”
Section: Why Should Object-naming Be Prepotent Over Color-naming?mentioning
confidence: 99%
“…Lederman et Klatzky, (1997) observent que des adultes travaillant sans voir peuvent discriminer un objet plus rapidement s'il diffère par la texture plutôt que par la forme. Cela a également été observé chez les enfants (Berger & Hatwell, 1996;Gliner, Pick, Pick, & Hales, 1969;Siegel & Vance, 1970). Berger et Hatwell (1993, 1995 Le système haptique semble donc plus adapté que la vision pour le traitement de la texture.…”
Section: Le Traitement De La Textureunclassified